The Role of Ferroptosis in the Treatment and Drug Resistance of Hepatocellular Carcinoma - Zhao, Siqi; Zheng, Wubin; Yu, Chao; Xu, Gaoxin; Zhang, Xinyi; Pan, Chao; Feng, Yongheng; Yang, Kunxing; Zhou, Jin; Ma, Yong (Frontiers in Cell and Developmental Biology, 2022)
Cell death is a fundamental feature of the development of multicellular organisms and a key driver of degenerative diseases. Ferroptosis is a new regulatory cell death mediated by iron-dependent lipid peroxidation, which is different from apoptosis and necrosis in morphology, pathophysiology and mechanism. Recent studies have found that ferroptosis is involved in the development of many diseases including hepatocellular carcinoma. The specific mechanisms of ferroptosis in hepatocellular carcinoma (HCC) are being revealed as further research progresses. In this review, we summarize these recent advances. In addition, we collate advances in the increasingly troublesome treatment direction of drug resistance in hepatocellular carcinoma and the latest treatments for ferroptosis-related HCC.